2009
DOI: 10.1111/j.1469-7580.2009.01125.x
|View full text |Cite
|
Sign up to set email alerts
|

Dimensions of forelimb muscles in orangutans and chimpanzees

Abstract: Eight forelimbs of three orangutans and four chimpanzees were dissected and the muscle mass, fascicle length and physiological cross-sectional area (PCSA) of all forelimb muscles were systematically recorded to explore possible interspecies variation in muscle dimensions. Muscle mass and PCSA were divided by the total mass and total PCSA of the entire forelimb muscles for normalization. The results indicate that the mass and PCSA ratios of the monoarticular elbow flexors (M. brachialis and M. brachioradialis) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
58
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(62 citation statements)
references
References 42 publications
4
58
0
Order By: Relevance
“…Although this seems a reasonable conclusion, the absence of such interspecific differences in our study highlights the importance of interindividual/intraspecific variation. Further, it underlines the need to continue increasing the dataset of ape muscle architecture to give a better appraisal of this variation, as the small sample sizes in both the present study and Oishi et al.’s (2009) have yielded different conclusions.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Although this seems a reasonable conclusion, the absence of such interspecific differences in our study highlights the importance of interindividual/intraspecific variation. Further, it underlines the need to continue increasing the dataset of ape muscle architecture to give a better appraisal of this variation, as the small sample sizes in both the present study and Oishi et al.’s (2009) have yielded different conclusions.…”
Section: Discussionmentioning
confidence: 76%
“…2004). Oishi et al. (2009) observed that their orangutan specimens had longer fascicles and smaller PCSAs in their digital flexors compared with chimpanzees.…”
Section: Discussionmentioning
confidence: 86%
“…The specimens listed in Table were dissected and muscle dimensions were determined as described in our previous reports (Oishi et al. ,b, ). During dissection, the muscles shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Other approaches to gorilla and orangutan anatomy have addressed function with quantitative information by focusing on one component, for example skeletal proportions (e.g., Schultz, 1930Schultz, , 1937Schultz, , 1956); biomechanics of scapula or limbs (e.g., Miller, 1932;Oxnard, 1967;Roberts, 1974;Taylor, 1997), regional muscle and limb weights and inertial properties (e.g., Preuschoft, 1961Preuschoft, , 1963Payne et al, 2006a, b;Isler et al, 2006;Oishi et al, 2008Oishi et al, , 2009). On live captive gorillas and orangutans, direct measures of muscle function or joint motion derive from electromyography during specific limb movements (e.g., Basmajian, 1974a, b, 1978;Tuttle et al, 1975;Stern and Susman, 1981;Tuttle et al, 1983) and from cinematography of climbing modes (e.g., Isler and Thorpe, 2003;Isler, 2005).…”
Section: Introductionmentioning
confidence: 99%